Stability Estimates for an Arithmetic Functional Equation with Brzdȩk Fixed Point Approaches - Heejeong Koh (Mathematics, 2023)
We introduce an arithmetic functional equation <semantics>f(x2+y2)=f(x2)+f(y2)</semantics> and then investigate stability estimates of the functional equation by using the Brzdȩk fixed point theorem on a non-Archimedean fuzzy metric space and a non-Archimedean fuzzy normed space. To apply the Brzdȩk fixed point theorem, the proof uses the linear relationship between two variables, x and y.